Prophylactic cavotricuspid isthmus block during atrial fibrillation ablation in patients without atrial flutter: a randomised controlled trial. Issue 12 (3rd March 2009) - Pontoppidan, J; Nielsen, J C; Poulsen, S H; Jensen, H K; Walfridsson, H; Pedersen, A K; Hansen, P S
Abstract : Objectives: This randomised trial evaluated if patients with atrial fibrillation (AF) and no history of atrial flutter (AFL) had any benefit of prophylactic cavotricuspid isthmus block (CTIB) in addition to circumferential pulmonary vein ablation (CPVA). Methods: 149 patients with AF (54% paroxysmal) were randomised to CPVA and CTIB (group CTIB+, n = 73) or CPVA alone (group CTIB−, n = 76). Patients were followed for 12 months with repetitive 7-day Holter monitoring after 3, 6 and 12 months. Results: Six patients (4%) had cardiac tamponade, and one patient had a stroke. No difference was found in the cumulative AFL-free rate between the two treatment groups (CTIB+: 88% vs CTIB−: 84%, hazard ratio (HR) 0.80, 95% CI (0.34 to 1.90), p = 0.61). There was no difference in the cumulative AF-free rate between the groups (CTIB+: 34% vs CTIB−: 32%, HR 0.93, 95% CI (0.63 to 1.38), p = 0.71). Overall, 33% of the patients were free of AF after a single procedure. Including reprocedures, a complete or partial beneficial effect was noted in 62% of the patients at 12 months. At 12-month follow-up, 24 (50%) patients with documented AF or AFL in the Holter recordings were asymptomatic. Conclusions: It was not possible to demonstrate any beneficial effect of CTIB in addition to CPVA with regard to AFL or AF recurrences during follow-up. Repetitive long-term Holter monitoring demonstrated a 33% rate of freedom from AF during a 1-year follow-up. Including additional CPVA procedures, a clinical effect was noted in 62% of the patients at 12 months. Patients with AF or AFL recurrences were often asymptomatic.